(untitled) (Journal of International Studies, 2020)
India has had a long history of relations with Myanmar (Burma) even prior to their independence, as both were British colonial possessions. Relations since Myanmar’s independence in 1948 were cordial such that both countries even shared similar views on non-alignment. Although in 1964, Myanmar nationalized privately-owned enterprises that negatively impacted on the livelihood of Indians in the country, relations between both remained cordial, though at times low key. In addition, Myanmar ’s self-imposed policy of isolation was another major reason for the state of relations between both during this period. In 1988, when major demonstrations against military rule rocked Myanmar, India became one of the major critics of the latter’s poor human rights record and a staunch advocate for the return of democracy to the country. It was obvious that for India, upholding its democratic ideals became the cornerstone of its policy toward Myanmar. However, since the early 1990s, India has changed its earlier stance to one that is currently shaped by geostrategic and geo-economic concerns. This shift has been due to at least three major factors namely the China factor and Myanmar ’s abundant natural resources.